Complementarity of neutron, XFEL and synchrotron crystallography for defining the structures of metalloenzymes at room temperature. (2022) - Moreno-Chicano, Tadeo; Carey, Leiah M.; Axford, Danny; Beale, John H.; Doak, R. Bruce; Duyvesteyn, Helen M. E.; Ebrahim, Ali; Henning, Robert W.; Monteiro, Diana C. F.; Myles, Dean A.; Owada, Shigeki; Sherrell, Darren A.; et al.
No abstract available